The Effect of Environmental Awareness, Green Competitive Advantage, and Green Habbit on Business Performance with Generic Strategy as Moderation - Sistya Rachmawati; Etty Murwaningsari; Suyono Suyono; Mazzlida Mat Deli (International Journal of Social Science and Business, 2025)
The research objectives are to analyze (1) The effect of environmental awareness, green competitive advantage, and green habbit on business performance. (2) Generic strategy moderates the effect of environmental awareness, green competitive advantage, and green habbit on business performance. This research method is carried out by taking secondary data, namely consumer non-cyclical sector companies listed on the Indonesia Stock Exchange, according to purposive sampling criteria during the 2021-2023 period so that the total sample is 249 observations using moderated regression analysis. This study employs a quantitative approach with panel data analysis using EViews software. The results showed that environmental awareness does not affect business performance, green competitive advantage has a positive effect on business performance, green habbit has a positive effect on business performance, green strategy does not strengthen the effect of environmental awareness, green competitive advantage and green habbit on business performance, so the moderating variable, namely green strategy, is included in the predictor moderator variable category. The control size variable does not affect business performance, while leverage influences business performance.